Estimation of Pavement and Bridge Damage Costs Caused by Overweight Trucks. Issue 1 (January 2014) - Dey, Kakan C.; Chowdhury, Mashrur; Pang, Weichiang; Putman, Bradley J.; Chen, Linbo
This study adopted a damage quantification framework to estimate bridge and pavement damage caused by overweight trucks. The framework was applied to estimate unit overweight truck damage costs for the highway system maintained by the South Carolina Department of Transportation. The analysis revealed that pavement and bridge damage increased significantly when trucks were above legal weight limits. Tradeoffs between the most common overweight truck fee types were estimated to examine their relative efficacy. The study found the axle-based damage cost recovery fee for the additional per trip damage cost above the legal weight limit for an overweight truck loaded up to the maximum overweight limit. The fee varied between $14 and $165 per trip, depending on the type of overweight truck. The flat damage cost recovery fee was $55 per trip for all overweight trucks (about two times the current flat damage fee in South Carolina). The study revealed that ignoring the axle distribution in the flat damage cost recovery fee caused some truck types to pay more and others to pay less than the actual damage they imparted. In a weight-based damage cost recovery fee system, the per trip damage cost recovery fee varied between $2.77 and $36.57 per ton; in a weight-distance-based damage cost recovery fee system, the damage fee varied between 2 and 14 cents per ton-mile. A comparative analysis between damage cost recovery fee types, such as the one presented in this paper, will provide insight to decision makers for setting policies regarding overweight trucking fees.